XALQ AMALIY SAN’ATIGA OID SO’ZLARNI O’ZBEK INGLIZ TILIDAGI MASALALARI (SYNAPSES: INSIGHTS ACROSS THE DISCIPLINES, 2024)
Folk applied art reflects the historical and cultural traditions of every nation. Uzbek folk applied art stands out with its unique patterns, techniques, and terminology. This article analyzes how terms related to Uzbek folk applied art are used and interpreted in other countries. Additionally, it provides a comparative analysis of how these terms are understood in different cultural contexts.